Regulation of RCC1 and its roles in apoptosis. - Li, Hoi Yeung. (2010)
This supplement equipment purchase grant is affiliated to the AcRF Teir 2 project ARC07/06. Although a number of signaling pathways have been identified to regulate apoptosis, the mechanism that initiates apoptosis remains incompletely understood. In this project, we aimed to study the possible regulation of the nuclear transport machinery to control the onset of apoptosis. We have found that the nuclear RanGTP level is diminished during early stages of apoptosis, which correlates to the immobilization of RCC1 on the chromosomes. Furthermore, the expression of phospho-mimic histone H2B or caspases activated Mst1 immobilizes RCC1 and causes reduction of nuclear RanGTP levels, which leads to the inactivation of nuclear transport machinery. As a consequence, nuclear localization signal (NLS) containing proteins, including NF-kB-p65, remain bound to importins α and β in the cytoplasm. Knocking down Mst1 allows resumption of nuclear transport and the nuclear entry of NF-kB-p65, which play important roles in rescuing cells from apoptosis. Therefore, we propose that RCC1 reads the histone code created by caspaseactivated Mst1 to initiate apoptosis by reducing the level of RanGTP in the nucleus. The findings in this project suggest that promoting apoptosis is the active disruption of nuclear trafficking before the cells are committed to the execution stages of apoptosis. It is believe that our findings lay the basis for a deeper understanding of how spatial and temporal signals are organized within apoptotic cells.